A hydroalcoholic blackberry leaf extract improved glucose tolerance and body composition and attenuated depression-like symptoms in ovariectomized rats. (Research, Society and Development, 2023)
Blackberry leaves (Morus nigra) are used in menopause to relieve hot flashes and night sweats and have been investigated in metabolic disorders. However, few studies investigated its effects on metabolic and behavioral disorders when associated with menopause. This study evaluated the effects of a hydroalcoholic extract of M. nigra leaves (MN) on body composition, glucose tolerance, and depression and anxiety-like behaviors in ovariectomized rats. For this purpose, 36 female Wistar rats were divided into groups: C – control; COvx – ovariectomized; MNOvx – ovariectomized and given MN at 400 mg.kg-1 body mass/day. Body composition was assessed by DEXA, glucose tolerance by the oral glucose tolerance test, and depression and anxiety-like behaviors by the forced swimming and elevated plus maze tests, respectively. Food intake and body mass gain were higher for MNOvx, followed by COvx and C (p